Óleo essencial de acessos de Varronia curassavica (Cordiaceae) como potencial agente de biocontrole e sobre Phytomonas serpens - Silva, Kleiton Paulo (2019)
The protozoa of the genus Phytomonas cause diseases in crops of agricultural and economic importance, however, there is still no control registered for these phytopathogens. The objective of this research was to evaluate the antiprotozoal activity of essential oil (EO) from seven Varronia curassavica genotypes and its morphophysiological effects on Phytomonas serpens promastigotes forms. The chemical analysis of the essential oils by gas chromatography with mass spectrometer GC-MS of the genotypes VC-002, VC-104, VC-202, VC-302, VC-303, VC-601 and VC-701, demonstrated that α-Pinene (56,69%), 7-Cyclodecen-1-ona.7-methyl-3-methylene-10-(1-propyl) (48,63%), Germacrene D-4-ol (32,16%), ar-Curcumene (20,37%),7-Cyclodecen-1-ona.7-methyl-3-methylene-10-(1-propyl) (19,32%), E-Caryophyllene (21,78%) e ar-Turmerone (28,36%) are the major compounds for each genotype, respectively. All the EO demonstrated antiprotozoal activity and the genotype VC-202 presented the lower IC50 (14μg/mL), presenting permanent effect against P. serpens. The images obtained in fluorescence microscopy and the data from fluorescence spectrophotometry using Propidium Iodide (PI), demonstrated cell alterations with permeabilization in cytoplasmic membrane. Through flow cytometry, it was demonstrated loss of mitochondrial membrane potential (Δѱm) in EO treated cells. The EO of different V. curassavica genotypes presented wide chemical variability and demonstrated antiprotozoal activity against P. serpens. Until the present moment, there are not reports about EOs activity against Phytomonas, therefore, the EO of genotype 202 is a potential source of raw material for formulations of bioproducts for Phytomonas control.